2017
DOI: 10.1111/bjh.14570
|View full text |Cite
|
Sign up to set email alerts
|

Phase I study of cord blood-derived natural killer cells combined with autologous stem cell transplantation in multiple myeloma

Abstract: Summary Multiple myeloma (MM) is a disease with known immune dysregulation. Natural killer (NK) cells have shown preclinical activity in MM. We conducted a first-in-human study of umbilical cord blood-derived (CB) NK cells for MM patients undergoing high dose chemotherapy and autologous haematopoietic stem cell transplantation (auto-HCT). Patients received lenalidomide (10 mg) on days −8 to −2, melphalan 200 mg/m2 on day −7, CB-NK cells on day −5 and auto-HCT on day 0. Twelve patients were enrolled, 3 on each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
133
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(139 citation statements)
references
References 44 publications
2
133
0
4
Order By: Relevance
“…These trials have collectively delivered over 300 infusions of expanded and activated NK cells to over 100 patients at doses up to 3 × 10 8 NK cells/kg and demonstrated early evidence of efficacy with no dose‐limiting toxicities. Three Phase I clinical trials have been completed—in patients with multiple myeloma undergoing autologous transplantation (NCT01729091), with AML/MDS receiving haplotransplantation (NCT01904136), and myeloid malignancies undergoing matched allogeneic transplant (NCT01823198, unpublished). A Phase II extension of the haplotransplant trial and two additional Phase I studies (in relapsed/refractory AML [NCT01787474] and pediatric brain tumors [NCT02271711]) are in progress.…”
Section: Clinical Applications Results and Toxicitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…These trials have collectively delivered over 300 infusions of expanded and activated NK cells to over 100 patients at doses up to 3 × 10 8 NK cells/kg and demonstrated early evidence of efficacy with no dose‐limiting toxicities. Three Phase I clinical trials have been completed—in patients with multiple myeloma undergoing autologous transplantation (NCT01729091), with AML/MDS receiving haplotransplantation (NCT01904136), and myeloid malignancies undergoing matched allogeneic transplant (NCT01823198, unpublished). A Phase II extension of the haplotransplant trial and two additional Phase I studies (in relapsed/refractory AML [NCT01787474] and pediatric brain tumors [NCT02271711]) are in progress.…”
Section: Clinical Applications Results and Toxicitiesmentioning
confidence: 99%
“…In NCT01729091, 29 patients with multiple myeloma undergoing autologous SCT with melphalan have received lenalidomide and infusions of NK cells expanded from cord blood in doses ranging from 5 × 10 6 to 10 8 /kg. Twelve patients treated during the Phase I dose escalation were reported, in which one patient had graft failure attributable to poor graft quality and there were no toxicities attributed to the NK cell infusions . Results of the Phase II portion of the study have not yet been reported.…”
Section: Clinical Applications Results and Toxicitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a small study in AML patients with impending relapse, Uharek et al showed favorable two-year survival (40% vs. 11%) when treated with a haploidentical transplantation in combination with post-transplant NK cell infusion, as compared to haploidentical transplantation alone. Also in multiple myeloma patients, NK cell were infused after both autologous and allogeneic transplantation [37,38] with no safety concerns.…”
Section: Post-transplantation Nk Cell Therapymentioning
confidence: 99%
“…Initial results of the study reported by Shah et al () merely support the safety of this approach, and in particular, an absence of graft‐versus‐host disease. They also present evidence that circulating NK cells can survive for up to 26 days.…”
mentioning
confidence: 95%